A comparative study for structural bedrock delineation by using conventional geophysical methods - ΠΑΠΑΔΟΠΟΥΛΟΣ, Τ. Δ.; ΑΛΕΞΟΠΟΥΛΟΣ, I. A.; ΚΑΜΠΟΥΡΗΣ, Π. Ι. (Bulletin of the Geological Society of Greece, 2001)
In this paper is examined the potential and effectiveness of two conventional geophysical methods in geotechnical research. The seismic refraction method that has been successfully used in the past for subsurface bedrock delineation in foundation projects, failed to indicate clear distinction between flysch and limestone bedrock material in the area under investigation. This failure is due to the macro-anisotropy structure of the limestone that resulted from joints, tectonic processes or/and karstic phenomena and later fillings of the voids with argillaceous material. The geoelectrical method of vertical sounding, on the other hand, although provided a clear distinction for the bedrock characterization, failed to distinguish the overburden cover from the underlain flysch formation. Finally, in this paper it is shown that for a successful application of geophysical work in geotechnical research, it is required effective design, utilization of modern analysis methods and handling more than geophysical methods.